Microstructural Analysis of Human White Matter Architecture Using Polarized Light Imaging: Views from Neuroanatomy - Axer, Hubertus; Beck, Sindy; Axer, Markus; Schuchardt, Friederike; Heepe, Jörn; Flücken, Anja; Axer, Martina; Prescher, Andreas; Witte, Otto W. (Frontiers in Neuroinformatics, 2011)
To date, there are several methods for mapping connectivity, ranging from the macroscopic to molecular scales. However, it is difficult to integrate this multiply-scaled data into one concept. Polarized light imaging (PLI) is a method to quantify fiber orientation in gross histological brain sections based on the birefringent properties of the myelin sheaths. The method is capable of imaging fiber orientation of larger-scale architectural patterns with higher detail than diffusion MRI of the human brain. PLI analyses light transmission through a gross histological section of a human brain under rotation of a polarization filter combination. Estimates of the angle of fiber direction and the angle of fiber inclination are automatically calculated at every point of the imaged section. Multiple sections can be assembled into a 3D volume. We describe the principles of PLI and present several studies of fiber anatomy in the human brain: 6 brainstems were serially sectioned, imaged with PLI, and 3D reconstructed. Pyramidal tract and lemniscus medialis were segmented in the PLI datasets. PLI data from the internal capsule was related to results from confocal laser scanning microscopy, which is a method of smaller scale fiber anatomy. PLI fiber architecture of the extreme capsule was compared to macroscopical dissection, which represents a method of larger scale anatomy. The microstructure of the anterior human cingulum bundle was analyzed in serial sections of 6 human brains. PLI can generate highly-resolved 3D datsets of fiber orientation of the human brain and has, therefore, a high comparability to diffusion MR. To get additional information regarding axon structure and density, PLI can also be combined with classical histological stains. It brings the directional aspects of diffusion MRI into the range of histology and may represent a promising tool to close the gap between larger scale diffusion orientation and microstructural histological analysis of connectivity.